Southern Ocean sea surface temperature synthesis: Part 1. Evaluation of temperature proxies at glacial-interglacial time scales - Chandler, David; Langebroek, Petra (Quaternary science reviews, 2021)
Quaternary interglacial climates are often used as analogues for how the Antarctic Ice Sheet will respond to future climate warming. Southern Ocean marine sediments provide an important paleoclimate archive in this respect. Sea surface temperature (SST) reconstructions in the Southern Ocean depend exclusively on the fossils or geochemical signatures of planktic organisms, but the strengths of these SST proxies remain poorly quantified in this region. To improve confidence in paleoclimate reconstructions, Part 1 of this two-part study evaluates the reliability of Southern Ocean SST proxies employed at Quaternary glacial-interglacial time scales, focusing on three key potential problems: advection/dispersion, seasonality, and non-thermal influences. We find that foraminifera assemblages and long-chain alkenones likely provide the most reliable SST reconstructions in this region. Diatom assemblages and the Globigerina bulloides Mg/Ca ratio are considered to be ‘moderately’ reliable. Both are subject to potentially significant non-thermal influences, and diatom assemblages are likely modified by species-dependent advection as they sink to the sea floor. Nevertheless, diatoms are valuable at higher latitudes, since alkenones and foraminifera assemblages lose sensitivity below ∼1 to 2 °C. Dinocyst assemblages, radiolarian assemblages, GDGTs and Neogloboquadrina pachyderma Mg/Ca are considered the least reliable in the Southern Ocean, due to weak calibrations, poorly-constrained non-thermal influences, and/or strong advection bias. We note that the seasonality of all proxies remains poorly constrained. Overall, Southern Ocean SST reconstructions using the recommended proxies and calibrations should be robust when averaging across multiple sites and proxy types, but should be treated with caution when analysing spatial variability, a small number of sites, or a single proxy type. Quantifying the effect of advection should be a priority for all planktic groups employed in Southern Ocean paleoclimate reconstructions. •Southern Ocean marine sediments are an important glacial-interglacial climate archive.•We review 7 sea surface temperature proxies available in the Southern Ocean.•We focus on advection, seasonality/depth, and non-thermal influences.•We recommend diatom and foraminifera assemblages, alkenones, and G. bulloides Mg/Ca.•We advise against analysing a small number of sites or a single proxy in this region.